(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: Dental status and oral hygiene are associated with progression of atherosclerosis in patients with carotid stenosis. It remains unclear whether dental disease is a risk factor for mortality in these patients.We evaluated the bearing of dental disease on mortality among patients with asymptomatic carotid atherosclerosis. METHODS: Three World Health Organization-validatedindices in 411 patients with asymptomatic carotid atherosclerosis were evaluated, measuring DMFT (decayed, missing, filled teeth) for dental status, CPITN (community periodontal index for treatmentneeds) for periodontal statusand SLI (Silness-LöeIndex) for oral hygiene respectively. Patients were prospectively followed for median 6.2 years (IQR 5.8 to 6.6 years) for all-cause mortality. RESULTS: During follow-up, 107 (26%) deaths occurred (74 cardiovascular causes). DMFT and SLI, but not CPITN, showed a significant and gradual association with mortality. For continuous variables, the adjusted hazard ratios (HR) for death were 1.06 (95% CI 1.0 to 1.12; p = 0.04) for DMFT, and 1.43 (95% CI, 1.01 to 2.03; p = 0.04) for SLI respectively. Edentulousness was a significant risk factor for death (adjusted HR 1.99, 95%CI, 1.18 to 3.02; p = 0.008). CONCLUSION: Dental status and oral hygiene were associated with mortality in patients with carotid atherosclerosis regardless of conventional cardiovascular risk factors.